The impact of corporate board size and board composition on corporate social responsibility disclosure in Nigerian non-financial sector: the moderation effect of firm's financial performance/ Shamsuddeen Yusuf Bugaje, Bala Sulaiman Dalhat and Mary Adaku Egbuna - Bugaje, Shamsuddeen Yusuf; Dalhat, Bala Sulaiman; Egbuna, Mary Adaku (Universiti Teknologi MARA Selangor, 2022)
The number of corporate social responsibility frameworks and principles has considerably increased both in academics and environments. The applications of corporate social responsibility disclosure (CSR) in Nigeria remain in developing form. Therefore, the main focus of this study is to investigate the relationship between corporate board size and board composition and corporate social responsibility disclosure with moderating effects of firm financial performance in the Nigerian listed non-financial companies. A dichotomous was utilized to develop an index based on the corporate social responsibility dimension, analysed and examined using content analysis. The sample data used in this study comprises of 62 companies in listed non-financial companies in Nigeria and for the period of five years (2015-2019). The data were examined by panel regression models. The result of the statistical analysis provides some evidence of a positive relationship between corporate board size, board composition, and corporate social responsibility disclosure. The finding from the study shows that Nigerian non-financial companies are more likely to disclose more information using corporate board size and board composition. The result of the joint interaction term of profitability as a moderator of financial performance reveals a strong moderating effect of profitability on the relationship between board size, board composition and corporate social responsibility disclosure with positive and statistically significant.